A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

GLOSSAQUA : A global dataset of size spectra across aquatic ecosystems - Zeynep Ersoy; Charlotte Evangelista; Aitor Larrañaga; Daniel M. Perkins; Javier Sánchez‐Hernández; Teofana Chonova; David Cunillera‐Montcusí; Carmen García‐Comas; Jorge García‐Girón; Ioar de Guzman; Justin Pomeranz; Victor Saito; et al. (Ecology, 2025)
Body size is a key trait in ecology due to its influence on metabolism and many other life‐history traits that affect population and community responses to environmental variation as well as ecosystem properties. The size spectrum represents the relationship between abundance (or biomass) and body size, independent of species identity. Size spectrum parameters, such as the slope or intercept, have been applied extensively as indicators of ecological status across multiple ecosystem types. The GLOSSAQUA dataset includes data from mainly heterotrophic communities composed of single (e.g., zooplankton, macroinvertebrates, or fish) to multiple taxonomic groups (e.g., from primary consumers to apex predators, and phytoplankton to large zooplankton), across diverse spatial and temporal scales, from surveys in freshwater (43% studies), marine (52% studies) and brackish (5% studies) ecosystems. In total, we compiled a unique global dataset of 8459 size spectrum slopes or exponents, 5237 intercepts, and 4,497 linearity coefficients (i.e., defined by the R 2 of the linear fit of the size spectrum) from 127 articles and gray literature (i.e., unpublished datasets). The current dataset aims to help identify the main drivers shaping aquatic size spectrum parameters at a global scale and contribute to cross‐ecosystem comparisons. GLOSSAQUA can serve to explore questions such as factors influencing spatial and temporal dynamics of community size structure, comparing the response of community size structure between natural versus human‐impacted sites, and comparing global patterns in different aquatic ecosystems. We encourage researchers, especially those from underrepresented geographical areas (e.g., South Hemisphere and Asia) to fuel this dataset in the future. The dataset is provided under a CC‐BY‐NC‐S4 4.0 license, and users are encouraged to cite this data paper when using the data.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Integrated modeling framework (FVCOM-ICM/Toxi) to simulate the fate and transport of polychlorinated biphenyls in urban estuaries–Case study for Puget Sound, WA - Lakshitha Premathilake; Tarang Khangaonkar; James West; Sandra O'Neill; Louisa Harding; C. Andrew James; Sukyong Yun; Kevin Bogue (Ecological Modelling, 2025)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

The Fourth Global Coral Bleaching Event: Where do we go from here? - James Davis Reimer; Raquel S. Peixoto; Sarah W. Davies; Nikki Traylor-Knowles; Morgan L. Short; Rafael A. Cabral-Tena; John A. Burt; Igor Pessoa; Anastazia T. Banaszak; R. Scott Winters; Tom Moore; Verena Schoepf; et al. (Coral Reefs, 2024)

Plenodomus tracheiphilus, but not Dothiorella ulmi, causes wilt disease on elm trees in Alberta, Canada - Yalong Yang; Heting Fu; Kher Zahr; Shiming Xue; James Calpas; Krista Demilliano; Michael W. Harding; David Feindel; Jie Feng (European Journal of Plant Pathology, 2024)

High-altitude characterization of the Hunga pressure wave with cosmic rays by the HAWC observatory - Ruben Alfaro; César Alvarez; Juan Carlos Arteaga-Velázquez; Arun Babu Kollamparambil Paul; Daniel Avila Rojas; Hugo Alberto Ayala Solares; Rishi Babu; Ernesto Belmont-Moreno; Chad Brisbois; Karen S. Caballero-Mora; Tomás Capistrán; Alberto Carramiñana; et al. (Advances in Space Research, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Correction to: MR Imaging in Ataxias: Consensus Recommendations by the Ataxia Global Initiative Working Group on MRI Biomarkers - Gülin Öz; Sirio Cocozza; Pierre-Gilles Henry; Christophe Lenglet; Andreas Deistung; Jennifer Faber; Adam J. Schwarz; Dagmar Timmann; Koene R. A. Van Dijk; Ian H. Harding; Astrid Adarmes-Gómez; Andreas Thieme; et al. (The Cerebellum, 2023)

The screening and prioritization of contaminants of emerging concern in the marine environment based on multiple biological response measures - C. Andrew James; Ruth Sofield; Maya Faber; Dave Wark; Amy Simmons; Louisa Harding; Sandra O'Neill (Science of The Total Environment, 2023)

MR Imaging in Ataxias: Consensus Recommendations by the Ataxia Global Initiative Working Group on MRI Biomarkers - Gülin Öz; Sirio Cocozza; Pierre-Gilles Henry; Christophe Lenglet; Andreas Deistung; Jennifer Faber; Adam J. Schwarz; Dagmar Timmann; Koene R. A. Van Dijk; Ian H. Harding; Astrid Adarmes-Gomez; Andreas Thieme; et al. (The Cerebellum, 2023)
With many viable strategies in the therapeutic pipeline, upcoming clinical trials in hereditary and sporadic degenerative ataxias will benefit from non-invasive MRI biomarkers for patient stratification and the evaluation of therapies. The MRI Biomarkers Working Group of the Ataxia Global Initiative therefore devised guidelines to facilitate harmonized MRI data acquisition in clinical research and trials in ataxias. Recommendations are provided for a basic structural MRI protocol that can be used for clinical care and for an advanced multi-modal MRI protocol relevant for research and trial settings. The advanced protocol consists of modalities with demonstrated utility for tracking brain changes in degenerative ataxias and includes structural MRI, magnetic resonance spectroscopy, diffusion MRI, quantitative susceptibility mapping, and resting-state functional MRI. Acceptable ranges of acquisition parameters are provided to accommodate diverse scanner hardware in research and clinical contexts while maintaining a minimum standard of data quality. Important technical considerations in setting up an advanced multi-modal protocol are outlined, including the order of pulse sequences, and example software packages commonly used for data analysis are provided. Outcome measures most relevant for ataxias are highlighted with use cases from recent ataxia literature. Finally, to facilitate access to the recommendations by the ataxia clinical and research community, examples of datasets collected with the recommended parameters are provided and platform-specific protocols are shared via the Open Science Framework.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Characterisation of Sweet potato collusive virus (SPCV) isolates from sweet potato (Ipomea batatas) in Australia - Amit C. Sukal; Sandra Dennien; Dawit B. Kidanemariam; Karlah Norkunas; Eric Coleman; Robert M. Harding; Anthony P. James (Australasian Plant Pathology, 2022)
Sweet potato collusive virus (SPCV) is a member of the genus Cavemovirus , family Caulimoviridae , for which only one full-length genome sequence has been reported. SPCV was first detected in Australia in 2007 in two sweet potato accessions using the nitrocellulose membrane ELISA kit developed by the International Potato Centre (CIP). Infected plants were also shown to contain isometric virions of ~ 50 nm, typical of members of the genera Cavemovirus , Caulimovirus , Petuvirus and Soymovirus . We have now sequenced and characterised the complete genomes of the two SPCV isolates (designated SPCV-Aus1 and -Aus2) using a combination of next-generation sequencing and PCR/Sanger sequencing. The sequences of both isolates encode three major ORFs with a genome organisation typical of cavemoviruses. However, isolate SPCV-Aus2 possesses a considerably shorter genome length of 7275 bp compared to SPCV-Aus1 (7712 bp) and the only available full-length sequence from a Portuguese isolate (7723 bp; GenBank accession number NC_015328). Further, ORF 1 of SPCV-Aus2 is considerably shorter than the ORF 1 length of both SPCV-Aus1 and SPCV-Mad1. Phylogenetic and PASC analysis showed that SPCV-Aus1 is closely related to SPCV isolates from North and Central America, whereas SPCV-Aus2 clustered together with isolates from Portugal and Africa.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

ASL expression in ALDH1A1+ neurons in the substantia nigra metabolically contributes to neurodegenerative phenotype - Shaul Lerner; Raya Eilam; Lital Adler; Julien Baruteau; Topaz Kreiser; Michael Tsoory; Alexander Brandis; Tevie Mehlman; Mina Ryten; Juan A. Botia; Sonia Garcia Ruiz; Alejandro Cisterna Garcia; et al. (Human Genetics, 2021)
Argininosuccinate lyase (ASL) is essential for the NO-dependent regulation of tyrosine hydroxylase (TH) and thus for catecholamine production. Using a conditional mouse model with loss of ASL in catecholamine neurons, we demonstrate that ASL is expressed in dopaminergic neurons in the substantia nigra pars compacta, including the ALDH1A1 + subpopulation that is pivotal for the pathogenesis of Parkinson disease (PD). Neuronal loss of ASL results in catecholamine deficiency, in accumulation and formation of tyrosine aggregates, in elevation of α-synuclein, and phenotypically in motor and cognitive deficits. NO supplementation rescues the formation of aggregates as well as the motor deficiencies. Our data point to a potential metabolic link between accumulations of tyrosine and seeding of pathological aggregates in neurons as initiators for the pathological processes involved in neurodegeneration. Hence, interventions in tyrosine metabolism via regulation of NO levels may be therapeutic beneficial for the treatment of catecholamine-related neurodegenerative disorders.

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

Production of selectable marker gene-free Cavendish banana (Musa spp.) using a steroid-inducible recombinase platform - Jennifer Kleidon; Anthony Brinin; Jean-Yves Paul; Robert Harding; James Dale; Benjamin Dugdale (Transgenic Research, 2020)
Genetic improvement of commercially accepted banana cultivars is strongly reliant on the ability to introduce genes that encode important agro-traits such as disease resistance. In most cases this can only be achieved using a transgenic approach. Public and regulatory acceptance of these events would greatly increase with “clean” single copy integration events free of the selectable marker gene and extraneous vector backbone. This would also allow for the successive addition of new genes and traits as they become available. In this study, we used the pMarker Free 1 (pMF1) vector containing the green fluorescent protein ( gfp ) reporter gene to assess the effectiveness of steroid-inducible recombination and positive/negative dual selection to regenerate transgenic Cavendish banana plants that were potentially free of the selectable marker gene. By examining the interaction of two different Agrobacterium strains with two different cultivars of Cavendish banana, namely Williams and Grand Naine, we describe a transformation and regeneration strategy that successfully produced marker-free, single transgene copy, gfp -expressing events. The system will provide a useful means of serially improving banana into the future.

Characterisation of a subgroup IB isolate of Cucumber mosaic virus from Xanthosoma sp. in sub-Saharan Africa - Dawit B. Kidanemariam; Amit C. Sukal; Adane D. Abraham; Joyce N. Njuguna; Benard O. Mware; Francesca Stomeo; James L. Dale; Anthony P. James; Robert M. Harding (Australasian Plant Pathology, 2019)

Molecular characterisation of a putative new polerovirus infecting pumpkin (Cucurbita pepo) in Kenya - Dawit B. Kidanemariam; Amit C. Sukal; Adane D. Abraham; Joyce N. Njuguna; Francesca Stomeo; James L. Dale; Robert M. Harding; Anthony P. James (Archives of Virology, 2019)

Production of membrane proteins for characterisation of their pheromone-sensing and antimicrobial resistance functions - Aalishaa A. Azam; Jean M. Kinder; G. Nasir Khan; Ade Alase; Pikyee Ma; Yang Liu; James R. Ault; Peter J. F. Henderson; Babur Z. Chowdhry; Bruce D. Alexander; Stephen E. Harding; Mary K. Phillips-Jones (European Biophysics Journal, 2018)

Characterization of an Australian isolate of taro bacilliform virus and development of an infectious clone - Dawit B. Kidanemariam; Amit C. Sukal; Kathy Crew; Grahame V. H. Jackson; Adane D. Abraham; James L. Dale; Robert M. Harding; Anthony P. James (Archives of Virology, 2018)

Transgenic cowpeas (Vigna unguiculata L. Walp) expressing Bacillus thuringiensis Vip3Ba protein are protected against the Maruca pod borer (Maruca vitrata) - Bosibori Bett; Stephanie Gollasch; Andy Moore; William James; Joel Armstrong; Tom Walsh; Robert Harding; Thomas J. V. Higgins (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Erratum to: Complete genome sequence of Colocasia bobone disease-associated virus, a putative cytorhabdovirus infecting taro - Colleen M. Higgins; Nicolas Bejerman; Ming Li; Anthony P. James; Ralf G. Dietzgen; Michael N. Pearson; Peter A. Revill; Robert M. Harding (Archives of Virology, 2016)

Complete genome sequence of a novel zantedeschia mild mosaic virus isolate: the first report from Australia and from Alocasia sp. - Dawit B. Kidanemariam; Adane D. Abraham; Amit C. Sukal; Timothy A. Holton; James L. Dale; Anthony P. James; Robert M. Harding (Archives of Virology, 2016)

Complete genome sequence of Colocasia bobone disease-associated virus, a putative cytorhabdovirus infecting taro - Colleen M. Higgins; Nicolas Bejerman; Ming Li; Anthony P. James; Ralf G. Dietzgen; Michael N. Pearson; Peter A. Revill; Robert M. Harding (Archives of Virology, 2016)

Anterior cingulate dopamine turnover and behavior change in Parkinson’s disease - Catherine L. Gallagher; Brian Bell; Matthew Palotti; Jen Oh; Bradley T. Christian; Ozioma Okonkwo; Jitka Sojkova; Laura Buyan-Dent; Robert J. Nickles; Sandra J. Harding; Charles K. Stone; Sterling C. Johnson; et al. (Brain Imaging and Behavior, 2015)

A Geoenvironmental Model for Orogenic Gold Deposits to Predict Potential Environmental Effects - Dave Craw; Jo Cavanagh; Joanna Druzbicka; Jon S. Harding; Gemma Kerr; James Pope; Dave Trumm (Mine Water and the Environment, 2015)

Hans Gocht (1930–2014) - James B. Riding; Susanne Feist-Burkhardt; Robert A. Fensome; Ian C. Harding; Jörg Pross (Palynology, 2015)

Isolation and functional characterisation of banana phytoene synthase genes as potential cisgenes - Bulukani Mlalazi; Ralf Welsch; Priver Namanya; Harjeet Khanna; R. Jason Geijskes; Mark D. Harrison; Rob Harding; James L. Dale; Marion Bateson (Planta, 2012)

Human Dimensions / Recreation and Ecotourism - Rachel Billingham; Marissa Jo Daniel; Francisco Aguilar; Hank Stelzer; Guy Robertson; Stanley Asah; Michelle King; Angela Gupta; Samatha Grant; Christopher Jones; Melanie Lenart; Richard Tholen; et al. (Journal of Forestry, 2011)
8With the current state of the economy and the budget woes found in everyone's workplace, every extra dollar we can use to offset the cost of projects counts—and what if those extra dollars came with public relations opportunities at no cost to you? For the last several years, the Pennsylvania Bureau of Forestry has cultivated relationships with a variety of non-traditional partners. These relationships have not only provided additional funds for tree planting projects through our TreeVitalize program, but have also provided fantastic public relations exposure and access to new audiences. Come hear how we used a “win-win” approach with our new partners and be inspired to try some of these ideas in your “neck of the woods.”

Cryoconservation of South African plant genetic diversity - Patricia Berjak; Paul Bartels; Erica E. Benson; Keith Harding; David J. Mycock; Norman W. Pammenter; Sershen; James Wesley-Smith (In Vitro Cellular & Developmental Biology - Plant, 2011)

A solid-state NMR study of the interaction of fish antifreeze proteins with phospholipid membranes - James Garner; Steven R. Inglis; James Hook; Frances Separovic; Margaret M. Harding (European Biophysics Journal, 2008)

Direct analysis of a GPCR-agonist interaction by surface plasmon resonance - Peter J. Harding; Timothy C. Hadingham; James M. McDonnell; Anthony Watts (European Biophysics Journal, 2006)

Molecular Analysis of Fiji Disease Virus Segments 2, 4 and 7 Completes the Genome Sequence - Robert M. Harding; Parichart Burns; Robert J. Geijskes; Richard M. McQualter; James L. Dale; Grant R. Smith (Virus Genes, 2006)

Molecular Analysis of Fiji Disease Fijivirus Genome Segments 1 and 3 - Richard B. McQualter; Grant R. Smith; James L. Dale; Robert M. Harding (Virus Genes, 2003)

The Potato Association of America - Steven R. James; Lori Wing; Ronald Knight; Barbara Harrity; Devid H. Lambert; Bud Platt; Al Reeves; Bill Bohl; Lind Sanford; Alexander D. Pavlista; Ed Plissey; Richard Sawyer; et al. (American Journal of Potato Research, 2000)

National Recreation Trails: A Forgotten Designation - Deborah J. Chavez; James A. Harding; Joanne F. Tynon (Journal of Forestry, 1999)
What value does federal designation add to open space resources that are not all federally owned and managed? Over the years the federal government, under the auspices of the National Park Service and USDA Forest Service, has designated trails across the United States as National Recreation Trails. A survey of federal, nonfederal public, and private National Recreation Trail managers indicated that few knew they maintained a federally designated trail. As a result, the managers could not use the designation to help them manage the trails. The time is right to revitalize this system.

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)